Anti-osteoporotic activity of harpagide by regulation of bone formation in osteoblast cell culture and ovariectomy-induced bone loss mouse models. (17th February 2016) - Chung, Hwa-Jin; Kyung Kim, Won; Joo Park, Hyen; Cho, Lan; Kim, Me-riong; Kim, Min Jeong; Shin, Joon-Shik; Ho Lee, Jin; Ha, In-Hyuk; Kook Lee, Sang
Abstract: Ethnopharmacological relevance: Harpagide, an iridoid glucoside, is a constituent of the root of Harpagophytum procumbens var. sublobatum (Engl.) Stapf, Devil's claw which has been used in patients with osteoarthritis (OA). In the present study, we investigated the anti-osteoporotic potential of harpagide and its underlying mechanism of action in in vitro cell culture and in vivo bone loss animal models. Material and methods: Harpagide was obtained from the alkalic hydrolysis of harpagoside, a major constituent of H. procumbens var. sublobatum Analysis of biomarkers for bone formation in osteoblastic MC3T3-E1 cells and bone resorption in osteoclast cells derived from mouse bone marrow cells was performed to evaluate the mechanism of action. The protective activity of harpagide against bone loss was also evaluated in ovariectomized (OVX) mouse model. Results: Harpagide improved bone properties by stimulating the process of differentiation and maturation of osteoblast cells and suppressing the process of RANKL-induced differentiation of osteoclast cells. In OVX-induced bone loss mouse model, oral administration of harpagide significantly improved recovery of bone mineral density, trabecular bone volume, and trabecular number in the femur. Harpagide also prevented increase of trabecular separation and structure model index induced by OVX. Harpagide effectively inhibited the serum levels of biochemical markers of bone loss, including alkaline phosphatase, osteocalcin, C-terminal telopeptide, and tartrate-resistant acid phosphatase. Conclusion: Taken together, the present study demonstrates that harpagide has a potential for prevention of bone loss in OVX mice by regulating the stimulation of osteoblast differentiation and the suppression of osteoclast formation. Therefore, these findings suggest that harpagide might serve as a bioactive compound derived from H. procumbens var. sublobatum for improvement of age-dependent bone destruction disease. Graphical abstract: